PENERAPAN ART OF DAKWAH UNTUK MENINGKATKAN MOTIVASI SISWA BELAJAR AGAMA ISLAM DI EKK MAN 1 CIANJUR - Wulandari, Fitri; Hoer, Uus Husni; Mutaqin, Dadang Zenal; Darmawan, Dicky (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
Currently, visual content spread worldwide often contains conspiracies serving the interests of certain groups to control humans, focusing their attention and belief on films and shows that promote disbelief. Therefore, the implementation of the Art of Da'wah to increase students' motivation to learn religion at MAN I Cianjur serves as a learning approach to convey Islamic messages and values to students. The purpose of this study is to facilitate students in learning Islam through art presented in digital form to dominate their daily habits. To build student motivation, there must be both internal (intrinsic) and external (extrinsic) encouragement. This study uses a descriptive quantitative method with a sample size of 47 people taken from a total population of about 88 people. Data collection techniques in this study include questionnaires, observations, interviews, and documentation. Data analysis uses SPSS with correlation formulas and Microsoft Excel assistance. The results of this study show an average value of 44.72 for the application of the Art of Da'wah, with an increase in motivation of 44.31, which can be interpreted as a high category. The degree of influence of X on Y is 0.89 or equivalent to 79.5%. The hypothesis proposed by the author: